When Religion Meets New Media : Media, Religion and Culture. - Campbell, Heidi (Religion, media, and culture series., 2010)
This lively book focuses on how different Jewish, Muslim, and Christian communities engage with new media. Rather than simply reject or accept new media, religious communities negotiate complex relationships with these technologies in light of their history and beliefs. Heidi A. Campbell suggests a method for studying these processes she calls the "religious-social shaping of technology" and students are asked to consider four key areas.